1999
DOI: 10.1016/s0003-6870(98)00018-0
|View full text |Cite
|
Sign up to set email alerts
|

Interface pressure and the prediction of car seat discomfort

Abstract: Citation: GYI, D. and PORTER, J., 1999. Interface pressure and the prediction of car seat discomfort. Applied Ergonomics, 30 (2) AbstractThe technique of interface pressure measurement has generated considerable interest in the automotive industry as a method, which could be used to predict driver discomfort during the development of prototype seat designs. Two repeated measures experiments were carried out to evaluate the practical application of the technique. The variables of foam density and posture were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 12 publications
3
63
0
3
Order By: Relevance
“…40 minutes is a relatively short time period in comparison to previous research that has suggested a duration of 2 hours is required to distinguish between seats (Gyi and Porter, 1999). The difference demonstrates that foam Type B performed significantly better than Type A in terms of discomfort ratings and signifying that Type B has better static and dynamics properties (combined).…”
Section: Effects Of Foam Compositionmentioning
confidence: 73%
“…40 minutes is a relatively short time period in comparison to previous research that has suggested a duration of 2 hours is required to distinguish between seats (Gyi and Porter, 1999). The difference demonstrates that foam Type B performed significantly better than Type A in terms of discomfort ratings and signifying that Type B has better static and dynamics properties (combined).…”
Section: Effects Of Foam Compositionmentioning
confidence: 73%
“…Previous research has recommended that driving trials have a duration of at least 2 hours to accurately determine the performance of a seat (Gyi and Porter, 1999;Porter et al, 2003). Porter et al (2003) demonstrated that although some seats are considered uncomfortable after 15 minutes, others that are initially considered comfortable become uncomfortable after about an hour; further highlighting the importance of long duration evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Porter et al (2003) demonstrated that although some seats are considered uncomfortable after 15 minutes, others that are initially considered comfortable become uncomfortable after about an hour; further highlighting the importance of long duration evaluation. Previous research into commercial vehicle driver discomfort has implemented trial durations ranging from 60 seconds to 135 minutes (Kolich, 2003a;Gyi and Porter, 1999), and findings demonstrate that temporal factors greatly influence driver discomfort as significant changes in overall discomfort have been observed at approximately 80 -110 minutes of driving (Gyi and Porter, 1998). This study intends to investigate a longer duration than previous research and also aims to encompass vibration, another important factor affecting driver discomfort (Mansfield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ability for a seat to accommodate a driver has been found to be related to the onset and magnitude of driver discomfort [9]. Further, the use of a lumbar support system has been shown to aid in the maintenance of a person's natural lordotic lumbar curvature during sitting [10,11] which has been associated with reducing lower back discomfort [12,13].…”
Section: Introductionmentioning
confidence: 99%